Out of Bounds and Out of Control : Regulatory Enforcement at the EPA. - DeLong, James V., 1938- (Rowman & Littlefield Pub. Group, 2002)
Out of Bounds, Out of Control measures the enforcement activities of the Environmental Protection Agency against that standard and finds them disturbingly deficient.